Assessing the energetic costs and trade-offs of a PHA-induced inflammation in the subterranean rodent Ctenomys talarum: Immune response in growing tuco-tucos - Cutrera, Ana Paula (2014)
A traditional approach used to assess whether immune defense is costly is to explore the existence of trade-offs between immunity and other functions; however, quantitative studies of the energetic costs associated with the activation of the immune system are scarce. We assessed the magnitude of a PHA-triggered immune response and the associated energetic costs in 60-day old Ctenomys talarum. We expected that the magnitude of the macroscopic inflammatory response to PHA is lower in young tuco-tucos compared with that of adults, given the allocation of substantial energy to growth, and that the magnitude of the inflammation is lower in male pups compared to females, due to the higher investment in growth of the larger sex. Concomitantly, we expected that the pups challenged with PHA show an increase in oxygen consumption compared to control animals and that a positive association exists between magnitude of the PHA-induced inflammation and oxygen consumption. Contrary to what was expected, young tuco-tucos mounted a higher inflammatory response compared with adults and there were no differences in the magnitude of this response between sexes. The inflammatory response induced by a PHA injection did not represent a significant energetic cost for young tuco-tucos. There were no differences in oxygen consumption between PHA-injected and control animals, and tuco-tucos that mounted a higher inflammatory response to PHA did not show higher oxygen consumption. Energy expenditure, however, is not the only physiological cost involved in trade-offs between immune response and various functions of the organism, and other currencies are discussed.